Method of handling indefinite factors in forecasting electricity load - Trinh, Trọng Chưởng (Journal of Technical Education Science, 2011)
The correlation between economic growth and electricity consumption still seems quite tight. But today, under the impact of energy prices and economical structure, these relationships have undergone many changes due to indefinite factors affecting the energy consumption: electricity price, population, housing area, etc... This article shows one of the mathematical methods of controlling and adjusting the regression coefficients in linear regression to determine and forecast electricity load demand: Gradient reduction methodology fastest